COVID-19 Variants of Concern in Australia, September 2020- April 2021 - Danielle Hutchinson; Hermione Williams; Haley Stone (University of New South Wales, 2021)
Variants of concern have been sequenced in Australia, through introduction via returned travellers (3). It has been shown that disease transmission and epidemic severity are directly related to variant emergence (82). It has also been shown that the mutations related to these variants confer resistance to neutralising antibodies, vaccine-induced or through previous infection (13). This Watching Brief summarises these issues, and asks key questions to guide Public Health policy regarding the vaccine and response strategies to variants of concern in Australia.